Effectiveness of a training program for the nursing staff on the oral health of institutionalised aged. Randomised trial. - Dairo Javier Marin Zuluaga; José Antonio Gil Montoya; Tiril Willumsen (Universidad Nacional de Colombia, 2019)
Background: it has been suggested that nursing-staff' should be educated in maintaining the oral health (OH) of institutionalised elder people. Objective: this work aimed for measuring the effectiveness of a 3-hour oral health training-programme (OHTP) provided to nursing-staff by assessing the residents' OH gains. Materials and methods: this was a one-year longitudinal-controlled-interventional study evaluated via a nursing-staff' questionnaire and residents' oral examinations. Managers of 30 nursing homes in Granada, Spain, were contacted and offered three oral examinations for their residents and an OHTP for the nursing-staff; nine of them consequently agreed to participate for all consenting people. 269 residents were examined at baseline and 12 months. After the baseline examination, the nursing homes were randomised into an intervention or control group; the OHTP was then carried out on the intervention group. Results: the residents' denture hygiene (p=0.03) and wearing of dentures at night (p=0.003) improved significantly in the intervention group; caries prevalence increased in both groups. Conclusions: the OHTP was effective for improving caregivers' knowledge and OH care routines, but the improvements were not enough to improve residents' overall OH.